1982
DOI: 10.1073/pnas.79.2.365
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tyrosine aminotransferase mRNA by glucocorticoids and cAMP in fetal rat liver.

Abstract: Tyrosine aminotransferase (L-tyrosine:2-oxoglutarate aminotransferase, EC 2.6.1.5) enzyme and mRNA activity were not detectable in day 20 fetal rat liver. Precocious induction of catalytic activity by in utero injection of dibutyryl cAMP was a direct consequence ofthe de novo appearance oftranslatable tyrosine aminotransferase mRNA. In contrast, in utero injection ofhydrocortisone acetate failed to elicit fetal liver enzyme activity. This failure was due to the inability of the steroid hormone to induce the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
1

Year Published

1982
1982
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
2
21
1
Order By: Relevance
“…Earlier work at the enzyme level has indicated that synthesis of the enzyme in fetal liver is not responsive to glucocorticoids [ Figure 5 show that the aminotransferase mRNA activity of unfractionated poly(A)-RNA from fetal liver remains undectable after glucocorticoid treatment, in accord with the failure of enzyme levels to change. Similar results have recently been reported by Ruiz-Bravo and Ernest [26]. By 24 hr after birth, after the differentiation event has occurred, the steroid-elicited response is readily observed in the translation assay.…”
Section: Aminotransferase Expression In Fetal Liversupporting
confidence: 90%
“…Earlier work at the enzyme level has indicated that synthesis of the enzyme in fetal liver is not responsive to glucocorticoids [ Figure 5 show that the aminotransferase mRNA activity of unfractionated poly(A)-RNA from fetal liver remains undectable after glucocorticoid treatment, in accord with the failure of enzyme levels to change. Similar results have recently been reported by Ruiz-Bravo and Ernest [26]. By 24 hr after birth, after the differentiation event has occurred, the steroid-elicited response is readily observed in the translation assay.…”
Section: Aminotransferase Expression In Fetal Liversupporting
confidence: 90%
“…This is accompanied by an increase in the newborn of hormones acting via the CAMP pathway, owing to postnatal hypoglycemia. These hormones seem to play a role in triggering the developmentally programmed onset of expression, as premature activation of the TAT gene can be elicited by administration of CAMP in utero (Greengard, 1970;Ruiz-Bravo and Ernest, 1982). TSEl activity, as determined by the fusion assay and Rla expression (data not shown) are high in mouse hepatoma ceils expressing fetal liver markers but low in adult hepatocytes (Gourdeau et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Premature induction of TyrATase activity can be elicited in fetal rats by in utero injection of Bt2cAMP but not by hydrocortisone (10). In contrast, both compounds induce TyrATase activity prematurely in fetal rat liver explants (11).…”
mentioning
confidence: 90%